INITIATIVES FOR ELIMINATING WASTE IN INDUSTRIAL KITCHENS - Novais da Silva, Fernando; Zimmermann, Guilherme; Prim, Pâmela; Amaral Reinert, Kamili (Revista Gênero e Interdisciplinaridade, 2025)
Brazil is one of the world’s largest food producers; however, it faces high levels of food waste across multiple sectors. In general, companies lack structured methods for quantifying waste, which hinders effective mitigation strategies. This article aims to present initiatives for reducing food waste in industrial kitchens. The methodology consists of an exploratory study conducted in companies located in Santa Catarina (Brazil) served by Organa Biotech. The results indicate that process improvements, methodological frameworks, technologies, and infrastructure enhancements can guide operations toward waste elimination when effectively implemented. The study concludes that adopting such initiatives is both feasible and beneficial, ranging from management tools to awareness programs focused on circular economy principles and the development of sustainable habits and practices. Organa Biotech performs on-site composting and also collects and shares data that reveal waste patterns across different operational areas, especially those related to food waste management. This research was supported by the Fundação de Amparo à Pesquisa e Inovação do Estado de Santa Catarina (FAPESC), through Public Call No. 50/2024 – Programa Impulsiona SC.